PENGARUH LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS PEGAWAI DINAS PEKERJAAN UMUM PROVINSI KALIMANTAN TIMUR - Nurrulloh, Mohammad (EKONOMIA, 2013)
Work environment in a private or government organization is very important to get attention. Although the work environment does not carry out the production process, but the work environment has a direct impact on the employees or officers of the production process. Focused work environment for its employees can improve performance and drive productivity otherwise inadequate working environment can degrade performance and eventually work motivation. The working environment is a factor that greatly affect the performance of employees. Pleasant working environment will realize the achievement of organizational goals and objectives.This study aims to: 1) Determine the influence of the physical environment and the non-physical environment on the productivity of the Public Works Department Employees of East Kalimantan Province; 2) Knowing that most of the factors affecting the productivity of the Public Works Department Employees of East Kalimantan Province.Fieldwork was conducted on the staff of the Division of Highways Department of Public Works East Kalimantan Province. Selected sample of 144 respondents. Regression analysis using the tool. Hypothesis testing using t-test and F test at 5% level.Conclusions of this study are: 1) hypothesis is rejected, where the physical environment and the non-physical environment does not significantly affect the productivity of the Public Works Department Employees of East Kalimantan Province. 2) Although partially occur significant influence, but when compared to the coefficient of variable physical environment has a greater influence than the non-physical environmental variables on the productivity of the Public Works Department Employees of East Kalimantan Province.